Beauveria bassiana FUNGUS AS A BIOLOGICAL ALTERNATIVE FOR THE CONTROL OF Bactrocera carambolae ON CHILI PLANTS - Helma Fitriani; Jantje Ngangi; Helen J Lawalata (Indonesian Biodiversity Journal, 2023)
Chili plants are an important horticultural crop for the Indonesian population. Still, in the context of pest control, the use of insecticides to manage the OPT is proving to be increasingly problematic for the environment and human health as a result of their ability to decimate microscopic organisms present in the soil so that as decomposers or decomposer microorganisms and earthworms perish, the soil would ultimately become more barren. Therefore, it needs to be overcome by finding other alternatives that are more environmentally friendly and reduce the negative impact of pesticides. This study aimed to determine an environmentally friendly alternative biological control using the Beauveria bassiana fungus. This study used an experimental method with five treatments and three replicates, notably spore concentration using B. bassiana 6g, 7g, 8g, 9g, and control. The use of this fungus is simple and does not incur significant costs. From the results of data collection, the Beauveria bassiana fungus is effective in killing carambolae with a fast mortality rate at a concentration of 9 g/500 ml of water (86.7%), and the slowest concentration is at 6 g/500 ml of water (63.4%).